Possible modification of Alzheimer’s disease by statins in midlife: interactions with genetic and non-genetic risk factors - Shinohara, Mitsuru; Sato, Naoyuki; Shimamura, Munehisa; Kurinami, Hitomi; Hamasaki, Toshimitsu; Chatterjee, Amarnath; Rakugi, Hiromi; Morishita, Ryuichi (Frontiers in Aging Neuroscience, 2014)
The benefits of statins, commonly prescribed for hypercholesterolemia, in treating Alzheimer disease (AD) have not yet been fully established. A recent randomized clinical trial did not show any therapeutic effects of two statins on cognitive function in AD. Interestingly, however, the results of the Rotterdam study, one of the largest prospective cohort studies, showed reduced risk of AD in statin users. Based on the current understanding of statin actions and AD pathogenesis, it is still worth exploring whether statins can prevent AD when administered decades before the onset of AD or from midlife. This review discusses the possible beneficial effects of statins, drawn from previous clinical observations, pathogenic mechanisms, which include beta-amyloid and tau metabolism, genetic and non-genetic risk factors (apolipoprotein E, cholesterol, sex, hypertension and diabetes) and other clinical features (vascular dysfunction and oxidative and inflammatory stress) of AD. These findings suggest that administration of statins in midlife might prevent AD in late life by modifying genetic and non-genetic risk factors for AD. It should be clarified whether statins inhibit Abeta accumulation, tau pathological features and brain atrophy in humans. To answer this question, a randomized controlled study using amyloid PET, tau-PET, and MRI would be useful. This clinical evaluation could help us to overcome this devastating disease.